A concise review on method development and validation parameters - Shipra Thapar; Anshul Chawla; Girish Kumar Gupta (GSC biological and pharmaceutical sciences, 2022)
Method development is a broad term. In both quantitative and qualitative analysis developing a new method either for estimation of quantity of substance or to check the presence of the required component is a necessitate step. Validation means to establish the characteristics parameters of the method. It also helps by revealing the limitations and their extent of the method. Both terms are essential to create and then establish for any drug component so that it can be used in any pharmaceutical industry for its benefit. Generally, the guidelines are followed as laid by ICH and USP which are followed worldwide. In this review article, some parts have been explained in reference to the subject quoted above.